ROLE OF HALOPHITE PLANTS IN SOIL PHYTOMELIORATION - Z.J.Isomiddinov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article presents information on the widespread use of halophyte plants in salinity reduction in areas with different degrees of salinity, i.e., medium, strong salinity lands, salt marshes, and the use of them to reduce the salt content of the soil.